Counselling Expectations of a Sample of East Asian and Caucasian Canadian Undergraduates in Canada - Fowler, Darren M.; Glenwright, Brittni J.; Bhatia, Maneet; Drapeau, Martin (Canadian Journal of Counselling and Psychotherapy, 2010)
This study investigated whether East Asians differ from Caucasian Canadians in their expectations about counselling. Participants in this study included 31 East Asian and 53 Caucasian Canadian university students. The East Asian participants were all first-generation East Asians living in Canada, originally from China, Korea, Japan, or Vietnam. The Caucasian Canadians were all born in Canada. All participants completed the Expectations about Counseling–Brief Form (Tinsley, Workman, & Kass, 1980), amongst other measures. Results indicated that Asians scored lower than Caucasians on client motivation and responsibility, but higher on the counsellor confrontation, directiveness, empathy, self-disclosure, expertise, and tolerance subscales. Clinical implications of these results and directions for future research are discussed.